Genetic Diversity and Population Differentiation of Guignardia mangiferae from “Tahiti” Acid Lime - Ester Wickert; Eliana Gertrudes de Macedo Lemos; Luciano Takeshi Kishi; Andressa de Souza; Antonio de Goes (The Scientific World Journal)
Among the citrus plants, “Tahiti” acid lime is known as a host of G. mangiferae fungi. This species is considered endophytic for citrus plants and is easily isolated from asymptomatic fruits and leaves. G. mangiferae is genetically related and sometimes confused with G. citricarpa which causes Citrus Black Spot (CBS). “Tahiti” acid lime is one of the few species that means to be resistant to this disease because it does not present symptoms. Despite the fact that it is commonly found in citric plants, little is known about the populations of G. mangiferae associated with these plants. Hence, the objective of this work was to gain insights about the genetic diversity of the G. mangiferae populations that colonize “Tahiti” acid limes by sequencing cistron ITS1-5.8S-ITS2. It was verified that “Tahiti” acid lime plants are hosts of G. mangiferae and also of G. citricarpa, without presenting symptoms of CBS. Populations of G. mangiferae present low-to-moderate genetic diversity and show little-to-moderate levels of population differentiation. As gene flow was detected among the studied populations and they share haplotypes, it is possible that all populations, from citrus plants and also from the other known hosts of this fungus, belong to one great panmictic population.